Clinical significance of positive anti‐neutrophil cytoplasmic antibodies without evidence of anti‐neutrophil cytoplasmic antibodies‐associated vasculitis. (6th February 2019) - Bornstein, Gil; Ben‐Zvi, Ilan; Furie, Nadav; Grossman, Chagai
Abstract: Aim: Anti‐neutrophil cytoplasmic antibodies (ANCA) have a role in the diagnostic workup of ANCA‐associated vasculitis. However, the clinical significance of positive ANCA in the absence of vasculitis is yet to be determined. Therefore, we sought to investigate the clinical spectrum and rate of patients with a positive ANCA without evidence of vasculitis. Methods: Retrospective analysis of patients positive for cytoplasmic ANCA (C‐ANCA) and proteinase 3 (PR3) or P‐ANCA and myeloperoxidase (MPO) between 2007 and 2016 in the Chaim Sheba Medical Center, Israel. The proportion of patients who had no evidence of vasculitis among all patients with a positive C‐ANCA/PR3 or P‐ANCA/MPO was calculated according to tertiles of enzyme‐linked immunosorbent assay (ELISA) antibody levels. Results: Among 113 patients who tested positive for C‐ANCA/PR3 or P‐ANCA/MPO, 68 (60.1%) had no evidence of vasculitis. ELISA antibody titers were significantly higher among patients with vasculitis than those without (6.2 vs 3.2, for C‐ANCA/PR3 and 5.4 vs 2.6 for P‐ANCA/MPO, P < 0.05). The proportion of patients without vasculitis among all patients with a positive C‐ANCA/PR3 and among all patients with a positive P‐ANCA/MPO declined in parallel to the increases in ELISA antibody level tertiles (96%, 57% and 22% in the 1st, 2nd and highest tertiles, respectively, for patients with C‐ANCA/PR3 patients and 100%, 66% and 20% in the 1st, 2nd and highest tertiles, respectively, for patients with P‐ANCA/MPO). Conclusion: A significant proportion of patients with a positive C‐ANCA/PR3 or P‐ANCA/MPO do not have evidence of vasculitis, particularly those with low‐medium ELISA antibody titers. Using a higher threshold of ANCA titers may be required to improve specificity.